Pediatric Endoscopy, Update 2020 - Dagmar Schreiber-Dietrich; Michael Hocke; Barbara Braden; Silvia Carrara; Uwe Gottschalk; Christoph F Dietrich (Applied Sciences, 2019)
Optimal management of pediatric endoscopy requires a multidisciplinary approach. In most hospitals, endoscopy in pediatric patients is performed by conventional gastroenterologists and only a few centers have specialized pediatric gastroenterologists. This is due to the fact that the number of pediatric gastroenterologists is limited and not all of them are experienced in endoscopic techniques. However, there are also some pediatric centers offering a high-quality and high-volume endoscopy service provided by very experienced pediatric gastroenterologists. Up to now, the literature on pediatric endoscopy is rather sparse. In this article, we describe current knowledge and practice of endoscopic procedures in pediatric patients, which should be relevant for both the adult and pediatric gastroenterologists.